229k views
5 votes
For each expression, (a) complete the square to make a perfect square trinomial, and (b) write the result as a binomial squared:

For each expression, (a) complete the square to make a perfect square trinomial, and-example-1
User Bart Read
by
7.0k points

1 Answer

4 votes
Explanation

i)

Completing the square

To find the missing term, we proceed as follows:


\begin{gathered} ax^2+bx+c\Rightarrow\text{ Standard form} \\ c=((b)/(2))^2 \end{gathered}

Then, we have:


\begin{gathered} c^2-16c+? \\ ?=\left((16)/(2)\right?^2 \\ ?=8^2 \\ ?=64 \end{gathered}

Thus, the perfect square trinomial is:


c^2-16c+64

The perfect square trinomial as a binomial squared is:


a^2-2ab+b^2=\lparen a-b)^2

In this case, we have:


undefined

Answer

User Vch
by
6.9k points